2019
DOI: 10.3389/fimmu.2019.02765
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Attenuates TLR3 Responsiveness and Impairs Anti-viral Mechanisms in Bronchial Epithelial Cells From COPD and Asthma Patients

Abstract: COPD and asthma exacerbations are commonly triggered by rhinovirus infection. Potentially promoting exacerbations, impaired anti-viral signaling and attenuated viral clearance have been observed in diseased bronchial epithelium. Oxidative stress is a feature of inflammation in asthma and COPD and is prominent during exacerbations. It is not known whether oxidative stress affects the anti-viral signaling capacity. Bronchial epithelial cells from asthmatic and COPD donors were infected with rhinovirus or treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 51 publications
4
27
0
1
Order By: Relevance
“…The objective of this study is therefore to investigate the effects of constant antiviral response activation due to incomplete viral clearance toward the motile ciliary formation and assembly in the nasal epithelium during re-epithelization following infection. This will enable us to establish the association between long-term effects of impaired viral clearance and ciliary impairment in perpetuating the symptoms of chronic airway inflammatory diseases ( Bryche et al, 2019 ; Menzel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study is therefore to investigate the effects of constant antiviral response activation due to incomplete viral clearance toward the motile ciliary formation and assembly in the nasal epithelium during re-epithelization following infection. This will enable us to establish the association between long-term effects of impaired viral clearance and ciliary impairment in perpetuating the symptoms of chronic airway inflammatory diseases ( Bryche et al, 2019 ; Menzel et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Asthmatic mouse models and in vitro cellular experiments showed that allergens or inflammatory cytokines could stimulate airway epithelial cell activation, which increased chemokine release, attracted inflammatory immune cell infiltration into the lungs, and induced ROS production in tracheal epithelial cells [8,50]. Animal experiments also showed that these inflamed immune cells released high levels of inflammatory mediators in the lungs and induced oxidative stress, which damaged lung cells and attenuated lung function [51,52]. In the present study, we found that sesamol inhibited ROS production in inflammatory BEAS-2B cells and reduced CCL11 and CCL24 expression, which inhibited eosinophil infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…DExD/H-Box Helicase 58 (DDX58), also known as reticonic acid induced gene I (RIG-I), activates and regulates the expression of various in ammatory factors, thereby initiating innate and speci c immune responses 20 . Many studies have shown that RIG-I plays an important role in the in ammatory response of asthma induced by viruses [21][22][23] . Human leukocyte antigen (HLA) is a gene complex closely related to human immune function.…”
Section: Discussionmentioning
confidence: 99%